Investigation of Genotoxic, Antimicrobial and Antioxidant Activities of Leaf and Flower Extracts of Cynara syriaca Boiss - Nurhüda Karaşin; Veysel Tolan; Nesrin Haşimi; Özlem Demirci (Journal of Agricultural Sciences)
The mutagenicity and antimutagenicity of leaves and flower extract of Cynara syriaca Boiss were studied with Ames assay in Salmonella typhimurium TA98 and TA100 strains. While leaves extract did not show any mutagenic effects against all the tester strains with or without metabolic activation, the flower extract showed mutagenic effect against TA98 strain without metabolic activation. On the other hand, it has been observed that the extracts have antimutagenic activity against mutations induced by sodium azide and daunomycin. The antimicrobial activity of extracts was determined by disc diffusion and MIC value. Both of the extracts possess weak antimicrobial activity. Cupric reducing antioxidant capacity (CUPRAC), DPPH free radical scavenging activity, and ABTS radical cation decolorization methods were carried out to determine the antioxidant activity. Among the tested antioxidant methods, the highest antioxidant capacity was determined in ABTS radical cation decolorization assay in which both of the extracts exhibited the best effect. Flower extract exhibited higher activity also in DPPH free radical scavenging.